New Understanding on an Old Compound: Insights on the Origin of Chain Sequence Defects and Their Impact on the Electronic Structure of AuCN. Issue 36 (21st August 2021) - Velasco‐Arias, Donaji; Mojica, Rodrigo; Zumeta‐Dubé, Inti; Ruíz‐Ruíz, Fabían; Puente‐Lee, Iván; Reguera, Edilso
Abstract: Gold cyanide, AuCN, despite its simple formula unit, has surprising structural features not completely understood to date. The present contribution discusses the results of a structural study on the nature of defects found in 1D AuCN when submitted to mechanical grinding. This is an appropriate treatment to induce structural defects in that solid, which were identified for the first time by combining XRD, XPS, Raman, and UV‐vis techniques. Furthermore, it is striking that the CN−Au−CN and CN−Au−NC sequences get disordered upon grinding while the NC−Au−CN gets ordered. Additionally, it is shown that the atomic chains apart from getting unraveled during the grinding process, are preferentially disrupted at the Au−N bond. The induced defects have a large impact on the UV‐vis absorption spectrum of AuCN. Abstract : Structural defects induced in AuCN (1D) through mechanical grinding. The CN−Au−CN and CN−Au−NC sequences get disordered upon grinding while the NC−Au−CN gets ordered. The atomic chains apart from getting unraveled during the grinding process, are preferentially disrupted at the Au−N bond. The induced defects have a large impact on the UV‐vis absorption spectrum of AuCN.